An unexpected re-arrangement of the antibiotic carbapenem core to new 1, 4-diazepin-5-one scaffolds. Issue 1 (19th December 2017) - Peters, Byron K.; Razuwika, Rufaro; Samipillai, Marivel; Arvidsson, Per I.; Kruger, Hendrik G.; Govender, Thavendran; Naicker, Tricia
Abstract : Herein we report a peculiar organocatalyzed domino-reaction on the carbapenem core structure. Abstract : Herein we report a peculiar organocatalyzed domino-reaction on the carbapenem core structure. As previously reported, 30 mol% of proline yields diazabicyclo[4.2.1]nonane analogues, while we currently report the formation of novel 1, 4-diazepin-5-ones from the same starting material in the presence of 100 mol% proline. The inherent chirality of the starting material led to the stereochemical preference of the products with excellent diastereoselectivity (>99 : 1). The diazepinone products were confirmed using X-ray diffraction and 2D-NMR structure elucidation. A plausible mechanism of the re-arrangement, involving an unactivated retro -Dieckmann condensation, is also presented.